2002
DOI: 10.1002/jrs.937
|View full text |Cite
|
Sign up to set email alerts
|

Weak polymer–electrolyte interaction revealed by Fermi resonance perturbed Raman bands

Abstract: A detailed analysis of isotropic and anisotropic Raman spectra of carbonyl stretching vibrations of ethylene carbonate in different systems was conducted. The variation of Fermi resonance perturbed spectral profiles was used to investigate changes in local molecular surroundings in polymer gel-electrolyte systems as a function of their composition. In poly(methyl methacrylate)-based gels it is found that the matrix interacts very weakly with the solvent molecules, ethylene and propylene carbonates, mostly play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
(19 reference statements)
2
10
0
Order By: Relevance
“…Fermi resonance perturbed Raman spectroscopy reveals there exists weak polymer-electrolyte interaction between poly-(MMA) and the solvent molecules, ethylene and propylene carbonate. [64] Ab initio molecular orbital calculations confirm that the hydrogen bonding hydration of the ionwater clusters to the polymers is destabilized by anions and stabilized by cations via ionic hydration in most cases. [65,66] The hydrogel volume transition is accounted for on the basis of electron-pair acceptance and electron pair donation change of water through ionic hydration.…”
Section: Molecular Simulationmentioning
confidence: 77%
“…Fermi resonance perturbed Raman spectroscopy reveals there exists weak polymer-electrolyte interaction between poly-(MMA) and the solvent molecules, ethylene and propylene carbonate. [64] Ab initio molecular orbital calculations confirm that the hydrogen bonding hydration of the ionwater clusters to the polymers is destabilized by anions and stabilized by cations via ionic hydration in most cases. [65,66] The hydrogel volume transition is accounted for on the basis of electron-pair acceptance and electron pair donation change of water through ionic hydration.…”
Section: Molecular Simulationmentioning
confidence: 77%
“…The cyclic carbonate functionality can be identified at 714 cm –1 in the ungelled polymer (black line). However, the peak at 718 cm –1 in the polymer–solvent mixture (Figure , blue line), which can be assigned to the skeletal bending mode of EC , is superimposing the investigated signal of the polymer matrix. Because of the overlapping of the two signals, it is not possible to identify the role of the cyclic carbonate group of the polymer matrix regarding lithium-ion solvation in the gel polymer electrolyte.…”
Section: Resultsmentioning
confidence: 96%
“…Interactions of interest involve those of the solvent-salt subsystem and, in particular, the diverse interactions between the polymer matrix and the electrolytic solvents as well as the conducting salt. In recent years, Raman and NMR spectroscopy represented the techniques of choice to study lithium-ion complexation in various polymer electrolyte systems. Additionally, pulsed field gradient (PFG)-NMR experiments were chosen by a number of researchers to determine the effect of the lithium-ion solvation on the ionic diffusivity in polymer based systems. …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In addition, spectroscopic studies have shown that this gel electrolyte is characterized by weak interactions between the solvent and the polymer matrix. The system we chose to study here, PMMA/ EC/ PC/ LiClO 4 , has the advantage that it has previously been investigated by various techniques.…”
Section: The Gel Electrolytementioning
confidence: 99%